Kapitał intelektualny nową wartością przedsiębiorstwa - Nycz, Małgorzata; Smok, Barbara (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
At the turn of the 20th and 21st centuries the role and importance of the enterprise knowledge rapidly rose. The intellectual capital becomes one of the most valuable asset within any enterprise. The paper has been devoted to this issue. It consists of 5 section. After short introduction to the problem, section two describes the knowledge based society. In section three the enterprise intellectual capital has been presented. Section four treats about new value of the enterprise generated through intellectual capital. The summary ends the paper. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 435-447